SPEAKING BERBASIS FOLKLOR UNTUK PENGEMBANGAN PARIWISATA - Hartono, Atrinawati (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2018)
ABSTRAK             Artikel ini akan  membahas Speaking berbasis folklor untuk pengembangan pariwisata. Speaking adalah kemampuan dasar untuk melakukan percakapan atau berkomunikasi menggunakan bahasa Inggris. Practicing everyday, stop being a student, use it or loose it, being able to communicate, and no need to worry in making mistakes, merupakan lima cara dasar untuk berlatih menggunakan bahasa  Inggris.  Folklor adalah cerita rakyat yang disampaikan secara turun temurun dan dapat digunakan sebagai media promosi pariwisata.. Ada tiga metode yang penulis gunakan  yaitu:  Asking for and Giving information, Asking for and Giving Direction, dan Asking for and Giving Opinion. Hasil Pembelajaran Speaking dapat digunakan untuk mempromosikan pariwisata setempat baik dalam lingkup lokal, nasional, maupun internasional. Kata kunci: speaking, folklor, promosi, pariwisata. ABSTRACT             This article will discuss about learning Speaking based on Folklore for developing tourism. Speaking is a basic skill for doing English conversation or making communication. Practicing everyday, stop being a student, use it or loose it, being able to communicate, and no need to worry in making mistakes, are five basic possibilities for practicing Speaking. Folklore is a traditional stories pass from one generation to the next generation, that can be used as a media for the promotion of tourism. The writer uses three methods namely:  Asking for and Giving information, Asking for and Giving Direction, and Asking for and Giving Opinion. The result shows that learning speaking can be used for promoting local tourism object, within the scope of local, national, and international. Keywords: speaking, folklore, promotion, tourism